PENERAPAN KEGIATAN BERNYANYI UNTUK MENGEMBANGKAN SOSIAL EMOSIONAL ANAK KELOMPOK B DI TAMAN KANAK-KANAK BUNGA TANJUNG DESA TANJUNG KECAMATAN BATHIN VIII KABUPATEN SAROLANGUN - Daraini, Salamah; Ridwan, Ahmad; Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social-emotional development is a fundamental aspect of early childhood growth that greatly influences children’s future quality of life. Preliminary observations at Bunga Tanjung Kindergarten, Tanjung Village, Bathin VIII District, Sarolangun Regency indicated that children’s social-emotional abilities were not yet optimal, as reflected in low self-confidence, limited social interaction, difficulties in cooperation, and limited emotional regulation. This study aimed to analyze the implementation of singing activities, particularly Islamic-themed songs, to develop the social-emotional skills of Group B children. The research employed a qualitative approach with a descriptive research design. The subjects of the study consisted of teachers and Group B children, while data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, and the validity of data was ensured through triangulation of sources, techniques, and time. The findings revealed that the planned and continuous implementation of singing activities created an enjoyable learning environment, increased children’s participation, and improved empathy, cooperation, and emotional control. However, several constraints were identified, including differences in children’s characteristics, limited learning facilities, and variations in teachers’ competence in managing singing activities. The study concludes that Islamic themed singing activities are effective as a learning strategy to support the development of social-emotional skills in early childhood education.